Combining cell transplants or gene therapy with deep brain stimulation for Parkinson's disease. Issue 2 (17th December 2014) - Rowland, Nathan C.; Starr, Philip A.; Larson, Paul S.; Ostrem, Jill L.; Marks, William J.; Lim, Daniel A.; Stacy (Chair), Mark; Lang, Anthony; Napier, Celeste; Samuel, Michael; Strafella, Antonio; Weintraub, Daniel
Abstract Cell transplantation and gene therapy each show promise to enhance the treatment of Parkinson's disease (PD). However, because cell transplantation and gene therapy generally require direct delivery to the central nervous system, clinical trial design involves unique scientific, ethical, and financial concerns related to the invasive nature of the procedure. Typically, such biologics have been tested in PD patients who have not received any neurosurgical intervention. Here, we suggest that PD patients undergoing deep brain stimulation (DBS) device implantation are an ideal patient population for the clinical evaluation of cell transplantation and gene therapy. Randomizing subjects to an experimental group that receives the biologic concurrently with the DBS implantation—or to a control group that receives the DBS treatment alone—has several compelling advantages. First, this study design enables the participation of patients likely to benefit from DBS, many of whom simultaneously meet the inclusion criteria of biologic studies. Second, the need for a sham neurosurgical procedure is eliminated, which may reduce ethical concerns, promote patient recruitment, and enhance the blinding of surgical trials. Third, testing the biologic by "piggybacking" onto an established, reimbursable procedure should reduce the cost of clinical trials, which may allow a greater number of biologics to reach this critical stage of research translation. Finally, this clinical trial design may lead to combinatorial treatment strategies that provide PD patients with more durable control over disabling motor symptoms. By combining neuromodulation with biologics, we may also reveal important treatment paradigms relevant to other diseases of the brain. © 2014 International Parkinson and Movement Disorder Society